Operational Management Analysis to Improve the Efficiency and Quality of Umrah Services at PT. Grand Shafa Nauli - Siti Hansyah Dewi Zai; Maidalena; Nuri Aslami (Danadyaksa: Post Modern Economy Journal, 2026)
The increasing number of Umrah pilgrims in Indonesia encourages travel organizers to ensure effective and efficient operational management to achieve optimal service quality. The existence of well-organized operational management plays a central role in ensuring smooth administrative affairs, punctuality of departure, and fulfillment of pilgrim comfort throughout the pilgrimage. This study applies a descriptive qualitative approach by collecting data through in-depth interviews. Based on the research results, it is known that operational management at PT. Grand Shafa Nauli is carried out through three main stages: planning, implementation, and supervision. From the perspective of the ideal operational management theory requires a comprehensive integration between resource planning, service delivery, and control mechanisms that run continuously. However, the reality in the field reveals a gap in the discipline of pilgrims in fulfilling payment obligations that has the potential to hinder the smooth operation of the operational chain, especially in the process of paying tickets and accommodation costs. This situation suggests that even though the planning framework has been thoroughly prepared, the implementation stage still faces risks originating from external factors, namely customer behavior patterns that are not fully under the company's control. In terms of service quality, pilgrims assess it based on three main aspects: staff friendliness, comfortable facilities, and punctuality in departure schedules. The presence of tour leaders and muthawifs as travel companions also contributes positively to the pilgrims' sense of security and satisfaction.